1979
DOI: 10.1007/bf01531742
|View full text |Cite
|
Sign up to set email alerts
|

Measuring musical abilities of autistic children

Abstract: Three normal children with reported musical ability and three autistic children were tested for the ability to imitate individual tones and series of tones delivered by voice, piano, and synthesizer. Accuracy of imitation was judged by two independent observers on the basis of pitch, rhythm, and duration. The autistic children overall performed as well as or better than the age-matched normal children. These results are discussed and their implications for future neurological and clinical research are consider… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
37
1
2

Year Published

2001
2001
2021
2021

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 79 publications
(41 citation statements)
references
References 5 publications
1
37
1
2
Order By: Relevance
“…Superior identification and labelling of pitch (Applebaum et al 1979;Bonnel et al 2003;Heaton et al 1998); enhanced sensitivity for pitch direction (Heaton 2005) and enhanced detection of changes in pitch contours (Heaton et al 2008) have been demonstrated by individuals with autism when compared to matched controls. On auditory discrimination tasks using music stimuli, Jones et al (2009) found that adolescents with autism performed as well as age and IQ matched controls; however a subgroup of individuals with autism demonstrated enhanced performance on the frequency discrimination task.…”
Section: Introductionmentioning
confidence: 95%
“…Superior identification and labelling of pitch (Applebaum et al 1979;Bonnel et al 2003;Heaton et al 1998); enhanced sensitivity for pitch direction (Heaton 2005) and enhanced detection of changes in pitch contours (Heaton et al 2008) have been demonstrated by individuals with autism when compared to matched controls. On auditory discrimination tasks using music stimuli, Jones et al (2009) found that adolescents with autism performed as well as age and IQ matched controls; however a subgroup of individuals with autism demonstrated enhanced performance on the frequency discrimination task.…”
Section: Introductionmentioning
confidence: 95%
“…Several studies showed that ASD-subjects are superior to typically developing subjects when it comes to detailed processing of musical structures (5) . Research of Heaton et al (6,7,8) , for example, showed that children with ASD outperform their matched controls on pitch discrimination, pitch categorization and pitch memory tasks.…”
Section: Anumberofstudieshavebeenaddressingtheroleofmusicforpeoplewitmentioning
confidence: 99%
“…In Kanner's (1943) description of 11 children with inborn autistic disturbances of affective contact, 6 showed an interest for music, and since that time, musical abilities have been considered as a relative strength in individuals with autism spectrum disorders (ASD), in comparison to their global profile (Applebaum et al 1979;Rimland 1964). Above-average auditory processing abilities, including enhanced pitch discrimination (Bonnel et al 2003;Heaton et al 1999b) and increased sensitivity to alterations of single pitches in a melody (Heaton et al 1999b; Mottron et al 2000) have been observed in children and adolescents with ASD.…”
Section: Introductionmentioning
confidence: 99%